Estudio de prefactibilidad para la instalación de una planta productora de yogurt griego con hojuelas de 7 semillas y miel de abeja - Chamorro Clemente, Aquelina Petronila (2023)
This study evaluates the commercial, technical, economic, financial and social viability of the installation of a Greek yogurt processing plant with flakes of 07 seeds sweetened with honey for the market of Metropolitan Lima. The project's demand for the 2026 is 3 623 037 containers of Greek yogurt with 7-seed flakes sweetened with honey in 250 gr presentation. The target audience is between 12- and 60-years old belonging to NSE A, B and C. The unit price of yogurt with cereal was established at S/ 4,5. For the location of the plant, it is in Lurín, in Lima, mainly due to the territorial area and the average price per square meter. The production process consists of several stages, being the raw material of the process 07 seed flour. The plant has an installed capacity of 3 994 055 units / year, which was defined by the inoculation activity. The total area for the plant is 480 ¿2. The project investment amounts to 3 132 175,4 Regarding the debt, this will be financed by the Interbank bank for 5 years at a TEA of 13,40% for long-term loans to large companies. The economic and financial evaluation of the project obtained an economic IRR of 42,66% with a recovery period of 2,32 years, while the financial flow an IRR of 53,15% with a recovery period of 2,01 years. Finally, it was determined that the social impact of the project through the product-capital ratio generates 3,38 soles of added value for each sol invested, therefore, the project will have a positive impact on the country's economy.